Application of Monoclonal Anti-Mycolate Antibodies in Serological Diagnosis of Tuberculosis - Alma Truyts; Ilse Du Preez; Eldas M. Maesela; Manfred R. Scriba; Les Baillie; Arwyn T. Jones; Kevin J. Land; Jan A. Verschoor; Yolandy Lemmer (Tropical Medicine and Infectious Disease)
Patient loss to follow-up caused by centralised and expensive diagnostics that are reliant on sputum is a major obstacle in the fight to end tuberculosis. An affordable, non-sputum biomarker-based, point-of-care deployable test is needed to address this. Serum antibodies binding the mycobacterial cell wall lipids, mycolic acids, have shown promise as biomarkers for active tuberculosis. However, anti-lipid antibodies are of low affinity, making them difficult to detect in a lateral flow immunoassay—a technology widely deployed at the point-of-care. Previously, recombinant monoclonal anti-mycolate antibodies were developed and applied to characterise the antigenicity of mycolic acid. We now demonstrate that these anti-mycolate antibodies specifically detect hexane extracts of mycobacteria. Secondary antibody-mediated detection was applied to detect the displacement of the monoclonal mycolate antibodies by the anti-mycolic acid antibodies present in tuberculosis-positive guinea pig and human serum samples. These data establish proof-of-concept for a novel lateral flow immunoassay for tuberculosis provisionally named MALIA—mycolate antibody lateral flow immunoassay.